2013
DOI: 10.28945/1773
|View full text |Cite
|
Sign up to set email alerts
|

YouTube: An Effective Web 2.0 Informing Channel for Health Education to Prevent STDs

Abstract: YouTube is a social media venue with great potential as a health education-informing channel. Health educators and the Centers for Disease Control and Prevention (CDC) (2011) recognize that YouTube enjoys a high level of engagement and comfort among young users. This enhances its educational value for this vulnerable population, who already account for half of the new sexually transmitted diseases (STDs) diagnosed annually. It is imperative to reach these users with information about safe sex and sexual risk p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This underscores the important Entertainment Education value that health communication practitioners may take advantage of. In as much as the health communication practitioners should be cautious of the risk of messages becoming trivial due to the application of humor, humorous messages has the potential of enhancing viewer attention, are more persuasive and can provoke positive viewer response (Prybutok, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This underscores the important Entertainment Education value that health communication practitioners may take advantage of. In as much as the health communication practitioners should be cautious of the risk of messages becoming trivial due to the application of humor, humorous messages has the potential of enhancing viewer attention, are more persuasive and can provoke positive viewer response (Prybutok, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Or perhaps the age of the viewer is important. Prybutok 47 found that teens and young adults feel more comfortable looking to the internet for medical information than discussing it with their parents or peers.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the age of people who would be most likely to be on the internet looking for information. As the Center for Disease control has stated, YouTube is a media well suited for younger consumers 47 and so it would make sense that they would be more likely to be depicted in this medium, even if they are not the ones most likely to consume healthcare products.…”
Section: Discussionmentioning
confidence: 99%
“…This results reinforced by the 2013 study by Prybutok, in which it confirms Youtube as a reference for its users to communicate and educates themselves about health. The use of Youtube as a channel for education and information has been deemed effective before [23].…”
Section: Tabel 3 the Respondent Reason For Using Preferences Mediamentioning
confidence: 99%